Patient and provider preferences for long-acting TB preventive therapy - M. Vermeulen; K.K. Scarsi; R. Furl; H. Sayles; M.J. Anderson; S. Valawalkar; A. Kadam; S.R. Cox; V. Mave; M. Barthwal; C. Schutz; A. Ward; et al. (IJTLD Open)
BACKGROUND: Tuberculosis preventive therapy (TPT) is critical for TB elimination but is underutilised. Long-acting (LA) TPT can potentially improve linkage to care, treatment adherence and outcomes. METHODS: We conducted a cross-sectional in-person survey in two high TB burden countries to evaluate preferences and concerns about LA formulations for TPT. The survey compared oral pills to LA injections, implants, and microarray patches (MAPs). A parallel online survey of healthcare providers (HCPs) in low- and middle-income countries (LMICs) assessed the perceived feasibility of implementation. Data were summarised by descriptive statistics. RESULTS: We recruited 409 patients (India, n = 209; South Africa, n = 200) and 94 HCP participants. The mean age of patients was 40 years; 65% were female, and 26% reported a history of TPT. Injectable LA-TPT was the most preferred modality, followed by pills, implants, and then MAPs. The majority (75%) expressed a strong willingness to try injectable LA-TPT. Among providers, 43% favoured injectable LA-TPT, 26% preferred oral pills, 18% implants, and 13% MAPs. Cost was a significant factor influencing HCPs’ willingness to adopt LA-TPT, while potential inefficacy and prolonged side effects were the highest concerns of patient respondents. CONCLUSION: Injectable LA-TPT may be highly acceptable and feasible if concerns surrounding cost, effectiveness, and safety are addressed.